The significance of free air co2 enrichment and open roof ventilatio greenhouse systems in a study of mealworm beetle, Tenebrio molitor L. (coleoptera: tenebrionidae) - Nur Hasyimah R.,; Nor Atikah A.R.,; Yaakop S., (Pusat Sistematik Serangga, Universiti Kebangsaan Malaysia, 2018)
Tenebrio molitor L. (Coleoptera: Tenebrionidae) is an insect storage pest that has been used as a subject in Integrated Pest Management (IPM) research. The aim of this study is to determine the importance of conducting insect-related studies, especially on T. molitor under a Free Air CO2 Enrichment (FACE) System and Open Roof Ventilation Greenhouse System (ORVS). FACE system provides a natural microclimate and biotic interactions, while ORVS is an artificial environment with regulation of its environmental parameters. More accurate comparisons can be made to the results obtained under the similar environmental factors including elevated CO2 concentration. Based on the results, the mortality time of T. molitor adults in ORVS (5-6 weeks) is the fastest, followed by FACE (9-10 weeks) and RR as a control (11-12 weeks). The highest significant time difference shows by the last adult individual dead is between ORVS versus RR is 6 weeks. Therefore, mortality rate of T. molitor adult and their life span are directly proportional to the elevated CO2 concentration. It is shows that the higher concentration of CO2, with faster mortality rate and shorter the life span of the adults. Since the study of insects using both systems is still limited, the data from this preliminary study can be used as reference for future research.